2010
DOI: 10.1007/s11668-010-9340-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Failure Analysis of a Broken Railway Axle: Effects of Surface Defects and Inclusions

Abstract: In the present work, the fatigue behavior of an axle was analyzed using modeling and experimental approaches. A failed axle was used for experimental studies. The experimental results were then analyzed in order to model and predict the fatigue life of axle. The three-dimensional finite element analysis was used to simulate the fatigue behavior of axle. The growth of a machining defect, 2 lm initial crack length, was simulated versus applied cycles. The changes in the stress intensity factor as a function of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…can be utilized. This model in its original form has been successfully employed by Alihosseini and Dehghani (2010) for the life prediction of a railway axle. The parameters C and n could be obtained for the material by conducting standard fracture tests like that suggested in ASTM E647-95 (1995).…”
Section: Through and Part-through Circular Cracksmentioning
confidence: 99%
See 1 more Smart Citation
“…can be utilized. This model in its original form has been successfully employed by Alihosseini and Dehghani (2010) for the life prediction of a railway axle. The parameters C and n could be obtained for the material by conducting standard fracture tests like that suggested in ASTM E647-95 (1995).…”
Section: Through and Part-through Circular Cracksmentioning
confidence: 99%
“…The fatigue failure of a railway axle in Turkey railway transportation system has been theoretically studied in Bayrakter et al (2010). The influences of surface defects and inclusions on the life of a failed railway axle has been studied in Alihosseini and Dehghani (2010) and revealed that the axle has been very sensitive to the surface machining scratches even if they are very small. Makino et al (2011) reviewed the fatigue damage tolerance of high-speed railway axles in Japan railway network and the crack growth behavior of an induction-hardened axle has been assessed based on the fracture mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Increase in the intensity of rail transportation leads to the increase of locomotive park usage and decrease its outage, including overhaul periods [1,2]. Such actions require review and extending of existing approaches in particular justification of fatigue life and crack growth resistance of railway axle steel [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…3 Treatment of cumulative fatigue damage has been received considerable attention in the past decades. [4][5][6][7][8] Existing models focus on the deterministic fatigue process, however, the fatigue damage accumulation in railway axles/components under service operation is stochastic in nature. This stochasticity is caused by the inherent variability in fatigue resistance of materials as well as the statistical nature of service loads experienced by the components.…”
Section: Introductionmentioning
confidence: 99%